The Cultural Contradictions of Middle Schooling for Rural Community Survival - Alan J. DeYoung; Craig Howley; Paul Theobald (Journal of Research in Rural Education, 1995)
Middle schools have been growing in popularity since the 1960s, and they are the only school type in the U.S. actually to have increased in number during the past 2 decades. Demographic changes, redistricting pressures related to desegregation, and economies ofscale rationales are probable causes behind the middle school movement. Educational leaders who advocate such schools, however, claim that middle schools have come into being because their instructional practices are better suited to the developmental needs ofchildren. We argue, conversely, that school reform in America historically has had little to do with the developmental needs ofchildren. Middle schools in both urban and rural places are attractive mostly for administrative, not pedagogical, reasons. Further, since the construction ofmiddle schools in many rural places often involves closing local elementary schools, the middle school concept does violence to communitarian precepts. In short, the middle school movement can be a real threat to citizens ofmany small towns, especially where their small elementary or high schools remain otherwise viable centers of community life.